PHYSICOCHEMICAL FACTORS AFFECTING PERSISTENCE OF FRANCISELLA TULARENSIS IN SOIL - J. Muhammad1; M. Rabbani; K. Muhammad; M. Wasim; A. Ahmad; A. A. Sheikh; F. Akhtar; A. Rasool; I. Khattak; T. Bashir; Z. U. Islam; M. Rasheed (Journal of Animal and Plant Sciences, 2017)
Francisella tularensis (FT) is gram negative, non-motile, capsulated and intracellular zoonotic fastidious bacteria, causing tularemia in both animals and human. Soil texture and heavy metals play an important role in survival and persistence of microbes in environment. In the present study, association of physical and chemical composition of soil was determined in 74 FT positive and negative sites in seven districts of Punjab, Pakistan. Soil samples were analyzed for macro and micronutrients including magnesium, copper, chromium, nickel, manganese, cobalt, lead, cadmium, sodium, iron, calcium, nitrogen, phosphorus and potassium by ammonium bicarbonate-diethylenetriaminepenta acetic acid (DTPA) method using atomic absorption spectrophotometer. Soil pH, moisture, clay, silt, sand, soluble salt and organic matters were determined using standard protocols. A significant difference was found in silt (21.49±14.36), clay (69.68±19.34), soluble salt (3.96±2.89), organic matters (7.32±3.95), nitrogen (0.37±0.20), nickel (1.06±0.23), cadmium (0.37±0.18), magnesium (1.51±3.44), lead (3.51±0.85) and zinc (0.56±0.19) in soil collected from both FT positive and negative sites. There was a non-significant difference in pH (8.21±1.93), sand (10.75±7.73), moisture (11.34±6.94), phosphorus (15.98±16.07), copper (0.23±0.18), chromium (0.38±0.97), manganese (1.99±9.15), iron (7.95±80.42), calcium (75.53±720.29), sodium (49.66±48.06) and potassium (43.59±37.66) in soil samples collected from all districts. In conclusion, physicochemical factors of soil play some role in persistence of FT in environment.
Keywords: Francisella tularensis; soil texture; heavy metals; spectrophotometer